Low incidence of posttransplant lymphoproliferative disorder after allogeneic stem cell transplantation in patients with lymphoma treated with rituximab. Issue 2 (3rd February 2020) - Fujimoto, Ayumi; Hiramoto, Nobuhiro; Yamasaki, Satoshi; Inamoto, Yoshihiro; Ogata, Masao; Sugio, Yasuhiro; Fukuda, Takahiro; Uchida, Naoyuki; Ikegame, Kazuhiro; Matsuoka, Ken‐ichi; Shiratori, Souichi; Kondo, Tadakazu; et al.
Abstract: Posttransplant lymphoproliferative disorder (PTLD) is a serious complication after hematopoietic stem cell transplantation (HSCT). Several studies of risk factors for PTLD have been reported; however, the probability of, and risk factors for, PTLD in patients with lymphoma is unknown. Japanese nationwide transplant registry data from 5270 patients with lymphoma after allogeneic HSCT were analyzed. Mature B‐cell, T/NK‐cell, and T‐cell lymphoblastic subtypes accounted for 49%, 26%, and 9.6% of lymphoma cases, respectively. Rituximab was used in 1678 lymphoma patients, most of whom (89%) received HSCT for mature B‐cell lymphoma. Thirty‐one patients with lymphoma developed PTLD, representing a probability of 0.77% at 2 years post‐HSCT, which did not differ significantly from that in patients with other diseases ( P = .98). Year of HSCT after 2010 (hazard ratio [HR] = 5.6, 95% confidence interval [CI], 1.48‐21.3), antithymocyte globulin (ATG) use in the conditioning regimen (HR = 4.5, 95% CI, 1.61‐12.5), and no rituximab use before HSCT (HR = 3.2, 95% CI, 1.26‐7.90) were identified as risk factors for PTLD. Probabilities of PTLD at 1 year post‐HSCT according to rituximab and ATG use were 0.23% (rituximab+, ATG−), 0.75% (rituximab−, ATG−), 1.25% (rituximab+, ATG+), and 3.53% (rituximab−, ATG+). Regarding lymphoma subtypes, patients with mature B‐cell lymphoma had the lowest incidence of PTLD (0.35% at 2 years). Among high‐risk patients receiving ATG, the mortality rate due to infection was elevated in those previously treated with rituximab (22%) relative to those without (14%); however, the difference was not significant ( P = .10). Rituximab use before HSCT significantly reduces the risk of PTLD. Adding rituximab to the conditioning regimen is potentially a good strategy to prevent the development of PTLD in high‐risk patients.